Iron, anaemia, and inflammatory bowel diseases. Issue 8 (9th July 2004) - Gasche, C; Lomer, M C E; Cavill, I; Weiss, G
Abstract : Iron deficiency anaemia is one of the most common disorders in the world. Also, one third of inflammatory bowel disease (IBD) patients suffer from recurrent anaemia. Anaemia has significant impact on the quality of life of affected patients. Chronic fatigue, a frequent IBD symptom itself, is commonly caused by anaemia and may debilitate patients as much as abdominal pain or diarrhoea. Common therapeutic targets are the mechanisms behind anaemia of chronic disease and iron deficiency. It is our experience that virtually all patients with IBD associated anaemia can be successfully treated with a combination of iron sucrose and erythropoietin, which then may positively affect the misled immune response in IBD.